Sustainability and ergonomics: cross-complex axis and quality of life - Varejão, Marcela (Acta Scientiarum Socialium, 2011)
Sustainability and ergonomics: cross-complex axis and quality of life. The object of this paper is to outline a complex projectual background to de¬sign, from the perspective of the interweaving of the human sciences with an Ergo¬nomics directed for the total quality of the human being, linked to sustainability as metaprinciple. Ergonomics and sustainability form thus a transversal axis of know¬ledge. This shaft is designed to produce a reflection on the ethical perspective in the projects. This percourse seeks to enhance the intellectual discourse of design and insert his actors as primary elements in the institutional frameworks of society. We may thus think then a future scenario whith designer as a catalyst between cultures and complex paradigms but also interacting with the "large areas" of governance. In this kind of design this "to be ergonomic" is placed as appositional quality in any design activity.
Keywords: design and ethics; design and politics; quality of life